Modeling post-socialist urbanization : the case of Budapest - Kiss, Daniel (Birkhauser, 2018)
The author examines the urban development of Budapest from 1990 to 2010. This period is characterized by the significant decline in communally town planning: given the structural legacies of socialist urbanization, the decentralization of government and resources, and the impact of a post-socialist culture struggle, a trend is being analyzed in which nebulous competencies lead to unclear and thus to a failure of higher-level planning. The ensuing consequence is an increase in large, investment-driven projects: it is characteristic of these privately financed projects that they do not submit to higher level control, in particular when these control bodies are rather weak. This model-based analysis presents the phenomenon as exemplary of the development in post-socialist cities.